Patterns of Communication Used by Special Education Teachers with Families of Handicapped Children - Abdel Aziz M. Sartawi (Journal of Islamic Studies, 1995)
The purpose of the study is to identify ways and types of communication used by special education teachers with families of exceptional children. To achieve this goal, a list of communication types was developed and distributed to special education teachers in the city of Riyadh. Results of the study indicated that most of the effective communication types are not used by special education teachers. In addition, differences in responses according to the variables of the study were also documented.